Note on the reduction of the rate of interest since 1870: with some remarks as to the probable amount of encumbrances on Irish land, and the possible fund available for their payment - Erck, Wentworth (Statistical and Social Inquiry Society of Ireland, 1889)
It is evident that capital invested either in mortgage, or in purchase, of land cannot expect to be exempt from the fate of capital invested in other securities. This fate is a steady, progressive, and of late rapid decline in the rate of interest yielded by all sound investments. Interest is only the net profit on capital, and as capital increases, interest decreases.
Read before the Statistical and Social Inquiry Society of Ireland, Tuesday evening, May 21st, 1889.
Keywords: Interest; Land valuation; 314.15